PENERAPAN METODE STORY READING MELALUI MODEL PEMBELAJARAN PICTURE AND PICTURE UNTUK MENINGKATKAN KEMAMPUAN BERBICARA ANAK USIA 5 - 6 TAHUN DI TK MUSTIKA BUNDA PEKANBARU - Armaita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This study aims to improve the speaking skills of children aged 5–6 through the story reading method using the picture-based learning model at TK Mustika Bunda Pekanbaru. The method employed in this study was classroom action research. The classroom action implemented by the researchers involved using the story reading method through the picture-based learning model to enhance the speaking skills of children aged 5–6, which was observed by an observer. The sample consisted of 20 children at TK Mustika Bunda Pekanbaru, including 13 boys and 7 girls. Data collection techniques included observation of teachers and children, as well as assessment of the speaking abilities of children aged 5–6 when using the story reading method through the picture-based learning model. The results showed that the story reading method could improve the speaking skills of children aged 5–6 years at TK Mustika Bunda Pekanbaru. The percentage increase in speaking ability from the first cycle to the second cycle was 20.5%. The implication of this study is that, when properly applied, the story reading method through the picture-based learning model can effectively enhance the speaking skills of children aged 5–6 at TK Mustika Bunda Pekanbaru.